Optically tunable filter based on meshed CDS‐polymer MIM capacitor. Issue 8 (27th May 2016) - Gonzalez, J. M.; Delhote, N.; Baillargeat, D.; McGarry, S. P.; Roy, L.
ABSTRACT: A new optically tunable low‐pass filter (LPF) is presented with a cutoff frequency ranging from 13.71 GHz to 14.79 GHz. Tunability is achieved based on a novel metal insulator metal (MIM) capacitor having a photorefractive insulator that shows 13% change in capacitance. The LPF has been fabricated and measured, and a simple lumped element model extracted to analyze its behavior. The improved meshed MIM capacitor employed in the LPF marks a practical demonstration of an optically tuned filter. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1926–1929, 2016